GURU DAN PEMBELAJARAN INOVATIF - Z Zunidar (STIT Al-Ittihadiyah Labuhanbatu Utara, 2018)
The existence of professional teachers is very strategic in planning, implementing and evaluating learning programs. Therefore, the management of learning in changing times is not just ordinary learning, but requires the development of learning models into innovative learning. Therefore, the teacher must have an innovative attitude to present innovative learning for improving the quality and learning outcomes. Thus professional teacher responsibility is a necessity to facilitate students to achieve superior results through effective innovative learning.